A Simple and Rapid Method for Quality Control of Major Histocompatibility Complex–Peptide Monomers by Flow Cytometry - Chandran, P. Anoop; Heidu, Sonja; Zelba, Henning; Schmid-Horch, Barbara; Rammensee, Hans-Georg; Pascolo, Steve; Gouttefangeas, Cécile (Frontiers in Immunology, 2017)
MHC-multimers are essential tools in T cell immunomonitoring which are employed both in basic and clinical research, as well as for assessing clinical samples during therapy. The generation of MHC monomers loaded with synthetic peptides is an elaborate and time-consuming process. It would be beneficial to assess the quality of these monomers prior to downstream applications. In this technical note, we describe a novel flow cytometry-based, cell-free, quick and robust assay to check the quality of MHC-monomers directly after refolding or after long-term storage.